Identification of loads in mechanical structures - helicopter case study - Uhl, Tadeusz (Computer Assisted Methods in Engineering and Science, 2002)
This paper presents possibility of identification of loads in mechanical systems based on response measurements during operation. Information of loads is very useful in diagnostic process, if usage of structure is under investigation. State of the art in the field of loads identification is presented. The problem of load identification is defined, and some methods are presented. The paper is focused on the problem of loads identification based on measurements of process parameters or movement parameters for vehicles or airplanes. Two methods are applied to show applicability of this approach in industrial practice; neural network based method and regression model based method. A case study of identification of load of helicopter structure during flight is presented.